Management of Obstetric Fistula: Experience of the Schiphra Hospital - Ouedraogo, D; Yaméogo, P; Kiemtoré, S (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To study the management of obstetric fistula Methods: Prospective and analytical cohort studycarried out at Schiphra Hospital in the period from 11 January to 31 August 2017. Results: The average age of women with obstetric fistula was 35.92 ± 9.80 years. 85.45% were housewives, 92.73% were out of school and 85.45% lived in rural areas. In about 43.64% of cases, obstetric fistula occurred in the first two pregnancies. The average age of fistula was 7.6 years with extremes of 2 months to 32 years. The average duration of labor was 53.29, resulting in caesarean delivery in 58% of cases and death of the newborn in 80% of cases. The complex fistula with 58.18% was the most common. The treatment constituted to a fistulorraphy in 63.64% of the cases. Therapeutic outcomes judged with a mean follow-up of 6 months were complete healing in 61.82%, stress urinary incontinence in 3.64% and failure in 34.54% of cases. Conclusions: Obstetric fistula is a reality in Burkina Faso today. The driving factor is the lack of adequate obstetric care. The Schiphra Hospital is engaged in its daily activities to eradicate it.